Сontrollability range of dielectric inhomogeneity located between the metal planes - Prokopenko Yu. V. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2012)
Controllability assessment of the characteristics of dielectric inhomogeneity, located between the metal planes, as part of micromechanically controlled microwave devices has been obtained. It is shown that with the micromovements of the metal plane over the dielectric, the effective dielectric constant of heterogeneity varies from the relative permeability value to one. The authors obtained smallness criteria of the thickness of dielectric or the frequency, at which the dielectric effect is not observed. The results can be used in design of electro-mechanically controlled microwave devices using piezoelectric and electrostrictive actuators and microelectromechanical system.